LiNbO3-Based Photonic FFT Processor: An Enabling Technology for SAR On-Board Processing - di Toma, Annarita; Brunetti, Giuseppe; Armenise, Mario Nicola; Ciminelli, Caterina (Journal of lightwave technology, 2025)
In the context of space applications, Synthetic Aperture Radar (SAR) systems can benefit from photonic systems, aiming to ensure higher performance and new functionalities, along with much greater compactness and lightness compared to commercial SAR systems, as required by New Space Economy constraints. To guarantee high spatial resolution imaging, which is essential in Earth Observation (EO), photonic SAR payloads are under development, and continuous investigation is underway to improve their performance. SAR payloads are realized by cascading microwave (MW) chirp generators, I/Q modulators, frequency up-converters, amplifiers, beamforming networks, Phased-Array Antennas (PAAs), and A/D converters for both transmission and receiving sections. To achieve a full-optical SAR, the A/D conversion in the receiving arm should be replaced by an optical system capable of performing processing directly onboard without passing through electronics. To elaborate SAR echoes several algorithms have been proposed exploiting Fast Fourier Transform (FFT) on digital samples. This paper introduces a novel photonic architecture able to realize an 8-bit Optical FFT (OFFT) overcoming the need for A/D conversion and reducing the overall Size, Weight, and Power Consumption (SWaP). The proposed solution has been investigated by taking into consideration features and constraints of current SAR payloads, guaranteeing 256 channels spaced 300 MHz apart in the Ka-band, with low propagation losses (2.8 dB/m), maximum insertion loss of 12 dB, maximum applied voltage of 7 V. maximum time delay of 0.98 ns, and tuners' length of 4.1 mm.